Efektifitas Metode Role Playing Pada Pembelajaran Pai Terhadap Penanaman Nilai Anti Korupsi Di Smpn 2 Ampek Angkek - Vivi Mavika Mulya; Wedra Aprison (STIKes Ibnu Sina Ajibarang, 2024)
The background of this research is that some students have not implemented instilling values corruption ​​in PAI learning. Like the dishonest behavior that appears among junior high school students by opening cheat sheets, asking friends. Based on this, the researcher applies the Role Playing method to PAI learning in instilling corruption values. This study also aims to determine the effectiveness of the Role Playing method in instilling anti-corruption values ​​at SMPN 2 Ampek Angkek. The hypothesis in this study is